Big kids: their meaning, development and importance in summerhill school - Goodsman, Danë (Revista Hipótese, 2017)
This article will be considering a particular societal aspect of A. S. Neill’s Summerhill School namely ‘Big Kids’. The effect of the Big Kid role on the social structure of the school means that children in Summerhill are not in the care of adults but actually in the care of other children.